Pola Manajemen dan Pengembangan Pegawai di Universitas Tangerang Raya - Azis, Nur; Fakih, Choerul (Innovative: Journal Of Social Science Research, 2024)
Employee management practices at Universitas Tangerang Raya have not been widely discussed, whereas studies on these practices need to be conducted for joint evaluation purposes. This study discusses the management practices of lecturers and employees based on indicators of recruitment, training, performance appraisal, career planning, job definition, employee participation, and compensation. The author uses a qualitative research method and data is obtained through observation, documentation, and in-depth interviews with leaders, lecturers, and employees of Universitas Tangerang Raya. The researcher found evidence that employee management practices based on indicators of recruitment, training, performance appraisal, career planning, job definition, employee participation, and compensation have been implemented quite well. What is new in this study is the strategy carried out by Universitas Tangerang Raya in managing employees effectively and efficiently to achieve the university's vision, mission, and goals. The approach used by Universitas Tangerang Raya to effectively and efficiently manage staff in order to fulfil the institution's vision, purpose, and objectives is novel in this study.